Revitalisasi Potensi Aren (Arenga pinnata merr.) di Kelurahan Abeli Kecamatan Nambo Kota Kendari Provinsi Sulawesi Tenggara - Laksananny, Satya Agustina; Rosmarlinasiah, Rosmarlinasiah; Basrudin, Basrudin; Nur, Hafidah; Tuwu, Eka Rahmatiah (Pakis Journal Institute, 2025)
This community service activity aims to increase the utilization of the areca palm (Arenga pinnata Merr.) through the application of modern cultivation techniques and strengthening the marketing of processed products. The activity is located in Tobimeita Village, Nambo District, Kendari City, Southeast Sulawesi, and the partner is the Forest Farmers Group (KTH). The main problem faced by the community is the conventional management of the sugar palm (Arenga pinnata Merr.) crop, which is limited to sap production. The solutions offered in implementing the 2025 Internal Community Service at Halu Oleo University include socializing cultivation techniques for fast-growing arenga palms, selecting superior seedlings, and diversifying processed products, so that the community in Tobimeita Village can increase household income. The results of the activity show high community participation in socialization activities related to the management of arenga palm trees, as well as collaboration between the Tobimeita Village Office and Halu Oleo University. In addition to socialization, Arenga palm (Arenga pinnata Merr.) seedlings were also distributed, and the activities were published in online media. This program is expected to promote the independence of productive businesses based on NTFPs (Non-Timber Forest Products), increase household incomes, and enhance the local community's competitiveness.